Development of Snack Bar from Black Soybean and Black Rice for Breastfeeding Mothers - Pramitasari, Rianita; Ivana, Ignatia; ., Yanti (International Journal of Engineering and Technology, 2019)
Breastfeeding mothers need more nutrients compared to mothers who are not breastfed to maintain quality and quantity of human milk they produce. Black soybean and black rice contain carbohydrate, protein, fat, and other nutrients that needed by breastfeeding mothers. The purpose of this study was to develop a snack bar for breastfeeding mothers. Snack bars were made from three ratio variations of black soybean flour: black rice flour (30:70, 50:50, and 70:30) with baking temperature 150 0C for 20 minutes. They were then subjected to sensory analysis (taste, flavor, color, texture, aftertaste, and overall); physical analysis (hardness, color); and chemical analysis (nutritional analysis, genistein, and daidzein). The results showed that snack bar with ratio 30:70 (black soybean: black rice) was preferred by panelists. Its level of hardness was 6.10±0.01 N. Its color was showed in color index L* = 25.04±1.71, a* = 6.05±0.70, b* = 3.89 ± 0.71, chroma = 6.66±0.25, and hue = 54.70±2.40. One serving (30 gram/serving) of this snack bar contained 16.28 grams of carbohydrate; 3.10 grams of protein; and 6.05 grams of fat. It could suffice 4.98 % of total energy based on Recommended Dietary Allowance of Indonesian breastfeeding mother per day. Meanwhile, the content of daidzein and genistein were 0.09 mg/serving and 1.35 mg/serving, respectively. In conclusion, snack bar from black soybean and black rice can be used as a complementary food for breastfeeding mothers due to its nutrient content and acceptability.